Clinicopathological correlation of liver biopsy- study of 50 cases (Journal of Dhaka Medical College, 2015)
Background: The liver biopsy is considered by many experts to be the most specific diagnostic tool used to assess the nature and severity of liver diseases such as hepatitis C. Liver biopsies are important for many reasons, such as accurate diagnosis or ruling out any coexisting liver diseases, staging and grading the severity of liver disease, treatment decisions, patient and provider reassurance, and as a benchmark for gauging future progression. Methods: In this observational study, 50 patients were recruited from different Medicine units of Dhaka Medical College Hospital, Dhaka, from May, 2008 to June, 2009. After preliminary selection of patients, a specific protocol was followed which include patients particulars, clinical features and clinical diagnosis, biochemical parameters, radiological and other investigative procedures and finally percutaneous needle biopsy of liver was done. The objective of the study was to establish the correlation of clinical presentation of chronic parenchymal liver disease with histopathological findings and establish liver biopsy as a tool for diagnosis. SPSS version 16.0 was used to analyze the data. Quantitative data were presented in the form of tables and figures. Chi-square test and student t test was done to find out the statistical significance. Results: Histopathologically chronic liver disease (CLD) was found to be the commonest lesion (pd0.05), which was 24 (48%) followed by hepatocellular carcinoma 13(26%) and secondary deposit 02(4%). Eleven cases consist of other findings including normal. CLD commonly presented with loss of appetite (82%), Jaundice (74%), Weight loss (68%), hepatic facies (54%).Hepatocellular carcinoma commonly presented with hepatomegaly (100%), jaundice (61.84%), weight loss (76.92%), and ascites (53.85%). Hepatomegaly was constant feature (100%) of all secondary metastasis. Among two cases of secondary carcinoma one (50%) was adenocarcinoma and another one (50%) was anaplastic type. Out of 29 cases of clinically diagnosed chronic liver disease 24 cases were confirmed histopathologically which was statistically significant (pd0.05). Conclusion: For the establishment of diagnosis and treatment it is mandatory to have a good correlation between clinical features and histopathological finding. Histopathology could detect diseases which were not considered clinically and specific management could only be done depending on histopathology. Therefore, if there is no contraindication, for confirmation of diagnosis liver biopsy still remains the corner stone modality. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21520 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 120-124